Evolution and structure of public and private funding of clusters in Europe: Results of three original independent questionnaire surveys - Peter Burger (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
Data collected from three self-administered questionnaire surveys conducted in 2011, 2016, and 2022 are used in this scientific paper. The paper aims to analyse the revenue structure of European clusters and focus on identifying possible differences in their funding in 2011, 2016, and 2022. Over eleven years, the revenue structure of clusters has changed to some extent, and the evolution and extent of these changes are the subjects of this paper. At the same time, it is necessary to determine whether the relatively high level of dependence of European clusters on public resources continues to persist or decreases or increases over time. The results show that the differences in the funding of the clusters studied in the selected years are statistically significant. The share of public and private funds has varied particularly over the last five years, and the share of public resources in cluster budgets has been steadily increasing. When comparing the shares of different public and private funding types, significant differences were observed for most clusters during the period under review. One of the few resources that have had a constant representation in cluster budgets over the whole period is the EU Structural Funds and Community Programmes, whose share in the budgets of European clusters has fluctuated only slightly, according to our statistical survey. Similarly, there has been no change in the share of credit instruments, such as bank loans, in cluster budgets. This share is consistently meagre in all three questionnaire surveys, which means that European clusters hardly use this funding source.
Keywords: O31; O38; R58; 330; Clusters; Cluster Policies; Financing Clusters; Public/Private Resources; Financial Structure